2016
DOI: 10.1186/s13100-016-0079-3
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering fact from artifact when using reporter assays to investigate the roles of host factors on L1 retrotransposition

Abstract: BackgroundThe Long INterspersed Element-1 (L1, LINE-1) is the only autonomous mobile DNA element in humans and has generated as much as half of the genome. Due to increasing clinical interest in the roles of L1 in cancer, embryogenesis and neuronal development, it has become a priority to understand L1-host interactions and identify host factors required for its activity. Apropos to this, we recently reported that L1 retrotransposition in HeLa cells requires phosphorylation of the L1 protein ORF1p at motifs ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 95 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Moreover, upon integration they could trigger antisense transcripts [ 19 ] or otherwise artificially trigger or disrupt silencing by mimicking actively transcribed, protein-coding gene. A recent study noted that differences in promoters, reporter sequences or integration sites could influence reporter expression and thereby affect the study conclusions [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, upon integration they could trigger antisense transcripts [ 19 ] or otherwise artificially trigger or disrupt silencing by mimicking actively transcribed, protein-coding gene. A recent study noted that differences in promoters, reporter sequences or integration sites could influence reporter expression and thereby affect the study conclusions [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used a protocol adapted from [60], where we first transfected siRNAs and then co-transfected siRNAs with L1 reporter plasmids. Besides functional validation of siRNAs, it is important to note that some 'non-targeting control' siRNAs (NTCs) are known to interfere with L1 retrotransposition, and their use should be avoided [61].…”
Section: (F ) Sirna-retrotransposition Assaysmentioning
confidence: 99%
“…Thus, we next optimized the L1 retrotransposition reporter protocol using siRNAs. Notably, a previous study demonstrated that widely used non-targeting control siRNAs (NTCs) could interfere with L1 retrotransposition [61]. The mechanism of the interference is unknown, and the use of these NTC siRNA controls should be avoided, at least in combination with the L1-retrotransposition reporter assay (see Methods for further details).…”
Section: (A) the Srna/l1-retrotransposition Reporter Assay Allows Testing On The Role Of Micrornas In L1 Activitymentioning
confidence: 99%